The Relationship Between Financial Ratios and Financial Distress - Roditri, Cholidul Ahmad; Yuliati, Anik; Sucahyati, Diarany (Gorontalo Accounting Journal, 2025)
This study aims to evaluate the impact of profitability, liquidity, and cash flow on financial distress in companies within the food and beverage sector listed on the Indonesia Stock Exchange (IDX) during the period of 2019-2023. The sample consists of 29 companies selected using purposive sampling, and data analysis is conducted using multiple linear regression and SPSS version 27. The results indicate that profitability (ROA), liquidity (CR), and cash flow (OCF) have a significant positive effect on financial distress. These findings provide valuable information for investors and management in efforts to manage financial distress risk in this sector.